2003
DOI: 10.1024/0300-9831.73.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable and Fruit: The Evidence in their Favour and the Public Health Perspective

Abstract: There is strong evidence that the intake of vegetables and fruits reduces the risk of cardiovascular disease (CVD) and is inversely associated with several forms of cancer. In contrast, information concerning specific macro- or micronutrients in relation to chronic diseases is limited and largely inconclusive. The beneficial role of vegetable and fruit consumption can also be inferred by considering the health effects of two dietary patterns, the Mediterranean and Japanese ones, in both of which the consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…This makes international comparisons more difficult. Some indexes postulate monotonic relations and do not take into account possible tolerance limits 48 . Another component-related problem is that the same importance is usually arbitrarily given to all index components, independently of the components' proportions in the diet and of the scientific evidence on the diet-disease relationship 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This makes international comparisons more difficult. Some indexes postulate monotonic relations and do not take into account possible tolerance limits 48 . Another component-related problem is that the same importance is usually arbitrarily given to all index components, independently of the components' proportions in the diet and of the scientific evidence on the diet-disease relationship 26 .…”
Section: Discussionmentioning
confidence: 99%
“…They may thus have a potential protective role in various chronic diseases, including common cancers (6)(7)(8)(9), and explain, at least in part, the well-established associations between high consumption of vegetables and fruit and reduced risk of several neoplasms (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…They have several biological activities that include antimutagenic, antiproliferative, and antioxidant effects, as well as involvement in cell signaling, cell cycle regulation, and angiogenesis (2,3). Consequently, flavonoids may have an important role in explaining the favorable effects of vegetables, fruit, and, possibly, tea against cancer (4)(5)(6). Two reviews (2, 7) of epidemiologic studies of flavonoid intake and cancer risk concluded that there is modest evidence that flavonoids are inversely associated with cancer risk, and that the evidence is more convincing for the flavonol quercetin and lung cancer.…”
Section: Introductionmentioning
confidence: 99%